Characterization of Water Repellent and Flame Retardant Finished Cotton Canvas Fabric for Bivouac T﻿ents. Issue 1 (January 2023) - Naeem, Farhana; Hussain, Muhammad Dawood; Khan, Danyal Rashid
Water repellency and flame retardancy have applications in many fields, such as automotive interiors, indoor decorations, upholstery, outdoor clothing and tents. Cotton, having superior qualities, is considered one of the best raw materials for tent manufacture. The study has undertaken the application of different water repellent and flame retardant chemicals on 100% cotton canvas fabric to be used as bivouac tents. The purpose was to find suitable water repellent and flame retardant chemicals that can be applied in a single bath or in a two-step process to give the desired repellency and retardancy effect. Initially, two screening sets were carried out, which aided in the identification of best-performed chemicals to be used in the combined application of water repellent and flame retardant. In the combined application, the fabric was finished using two approaches. In the first approach, both repellent and retardant chemicals were prepared in a single bath, and in the second approach, the fabric was first finished with flame retardant chemicals and then finished with water repellent chemicals. In both the approaches, the finished fabric was evaluated by a cone test, a hydrostatic pressure head test and a flammability test against locally set requirements. It is concluded that the procedure of single bath water repellent and flame retardant finishes (SBWRFR1b) showed reduced pickup percentage (60%) and resulted in better water repellency and flame retardancy properties, in comparison to other procedures and series of recipes.